Analisis mutu ikan koi menggunakan metode Statistical Process Control di Mizumi Koi Farm Sukabumi - Florra Grachya; Kharisma Fitri Hapsari; Mutiara Seftia Alzahra; Rayhan Raffi Lesmana; Siva Aulia Septianingsih; Velliza Jabbar Al Khanza (Journal of Innovative and Creativity, 2025)
This This study aims to analyze the quality control system of koi fish production at Mizumi Koi Farm Sukabumi using the Input–Process–Output (IPO) approach and quality control tools such as checksheets, Pareto diagrams, and Fishbone diagrams. This approach was applied to identify the key factors influencing koi fish quality and determine effective corrective actions. The results indicate that product quality is mainly affected by broodstock quality, water stability, and the consistency of maintenance procedures. The most dominant issues found were sudden larval mortality and unhatched eggs caused by unstable water temperatures and suboptimal handling during the hatching stage. Through disciplined implementation of quality control systems, digitalization of production records, and improved pond management, Mizumi Koi Farm successfully enhanced fish survival rates and maintained color consistency. This research highlights the importance of sustainable quality management as a means to increase production efficiency, strengthen competitiveness, and maintain the reputation of Sukabumi’s koi fish in both domestic and international markets.